Analisis Pengaruh Bauran Pemasaran 7P terhadap Keputusan Pembelian Produk Selada Hidroponik CV. TFP - Yulvika Fitriannas; Mukson Mukson; Kustopo Budiraharjo (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to ascertain the 7P marketing mix achievement rate of respondents and examine how the 7P marketing mix influences consumers' decisions to buy hydroponic lettuce products of CV. TFP. The research was conducted in August 2022, located at Jl. Tejosari Raya No. 1 Gedawang, Kec. Banyumanik, Semarang, Central Java. The location was selected purposefully based on the consideration of the CV. TFP is a hydroponic plant cultivation and marketing business with its superior products of hydroponic fruits and vegetables. The survey method was the research method that was used. The process of selecting the respondents involved using an accidental sampling technique of as many as 100 samples who were consumers purchasing CV. TFP hydroponic lettuce products directly at CV. TFP. Primary data was collected through consumer-distributed questionnaires used in interviews. Secondary data were obtained from BPS and other relevant sources. Multiple linear regression statistical tests and descriptive analysis are used for data analysis. In a multiple linear regression analysis, price, location, product, promotion, physical evidence, people, and process are independent factors (X), and the purchase decision is dependent (Y). The findings demonstrated that the Respondent Achievement Rate (TCR) value for the seven marketing mix factors (7P) is in the excellent range. The factors influencing purchasing decisions are people / human resources, process, product, price, place, and physical proof. Promotion is the only variable that has no effect. With a Standardized Coefficients Beta value of 0,241, the place variable is the most prominent 7P marketing mix variable.